Systemic barriers: the challenges in the provision of inclusive school libraries in Malaysia - Abrizah, Abdullah; Ahmad, R. (Faculty of Computer Science & Information Technology, University of Malaya., 2010)
Special Education Needs (SEN) students who have difficulties in learning have traditionally been marginalized within or even excluded from the school libraries. To explore the practices of the school library media service provision and programmes conducted for SEN students in the mainstream schools and understand conditions that may facilitate or deter the provision of an inclusive school library in a Malaysian setting, a total of 24 participants comprising special educators, teacher librarians and students with disabilities were interviewed. The study found that although examples of good practice of school library services and programmes were found, there is need for improvement in service delivery to SEN students. Much of this could be achieved by enhanced communication and cooperation between teacher librarians and special educators. The analysis suggests six barriers in the provision of inclusive school libraries: physical, resources, curriculum, policy, unintentional and intentional attitudinal barrier. The paper concludes with a consideration of possible strategies for improvements in provision of inclusive school libraries. It is hoped that the results will stimulate and encourage moves to create more effective and inclusive library arrangements for students with disabilities.